An ecological worldview as basis for a regenerative sustainability paradigm for the built environment. (16th December 2015) - Du Plessis, Chrisna; Brandon, Peter
Abstract: It has been widely argued that in order to move development into a positive curve towards sustainability, society needs to change the worldview/paradigm within which it currently operates; and that such a shift from a mechanistic to an ecological/living systems worldview is already happening. It is suggested that the purpose of the sustainability paradigm flowing from this worldview is not to conserve the status quo or meet ill-defined human needs, but to strengthen the health, adaptive capacity, and evolutionary potential of the fully integrated global social-ecological system so that it can continue regenerating itself, thereby creating the conditions for a thriving and abundant future – not only for the human species, but for all life. In this paper we explore the ecological worldview and the guidelines it provides for how we interpret sustainability; as well as the strategies for the production of the built environment we need to follow if we are to adapt to coming changes in the planetary system and regenerate the world. The question this paper asks is: how does this sustainability paradigm, with its focus on regenerating the whole of the social-ecological system within which we are working, change the way the built environment is produced? To achieve this objective, the paper synthesizes the findings of two separate studies: an extensive literature review to define the meta-narratives of the ecological worldview; and an analysis of in depth interviews with academics and built environment practitioners that aimed to find correlations between the practice and theoretical positions of the participants and the values and praxiology of the ecological worldview as described in the first study. Three main themes of the ecological worldview – wholeness, relationship, and change – provide a framework for discussing the implications of this regenerative sustainability paradigm for the production of the built environment – for how it is created, the technologies used, and how it is evaluated. Highlights: The three main themes of the ecological worldview: wholeness, relationship, change. Purpose of the regenerative paradigm: to increase the potential of the whole system. Reintegrate humans with nature through biophilic design that partners with nature. A co-created project acts as catalyst for on-going regeneration and evolution. The driving question: how can I contribute to a thriving and abundant future?